2019
DOI: 10.1007/s40430-019-2028-9
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective optimization of WEDM using cold treated brass wire for HSLA hardened steel

Abstract: The present study analyzed the effects of cold treated brass wire electrode for the machining of hardened high-strength low-alloy (HSLA) steel on wire electric discharge machine. Cold treatment of brass wire at − 70 °C for 24 h has refined its microstructure which results in an increase in electrical conductivity by 24.5%. The experimental work is designed using fractional factorial design to determine the relationship of input variables including servo voltage (SV), pulse on time (T on), pulse off time (T off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 65 publications
(76 reference statements)
0
5
0
Order By: Relevance
“…In this investigation work, it is evident that all the results of the analysis discussed above are in line with those results reported in various literature. 6,1517,19,2326 The variation of entry hole diameter with servo feed rate and wire feed rate is illustrated in Figure 10. Similarly, the relationship of servo feed rate and T on time with exit diameter is depicted in Figure 11.…”
Section: Analysis and Interpretation Of Experimental Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this investigation work, it is evident that all the results of the analysis discussed above are in line with those results reported in various literature. 6,1517,19,2326 The variation of entry hole diameter with servo feed rate and wire feed rate is illustrated in Figure 10. Similarly, the relationship of servo feed rate and T on time with exit diameter is depicted in Figure 11.…”
Section: Analysis and Interpretation Of Experimental Resultsmentioning
confidence: 99%
“…In another longitudinal study, the effect of both cold-treated and non-cold-treated brass wire (0.3 mm diameter) along with other input parameters on the cutting speed, surface roughness, and kerf width was studied by Tahir et al. 19 through WEDM of high-strength low-alloy (HSLA) steels. The objective behind selection of cold treated wire is that to enhance the electrical conductivity of the wire by 24.5%, this could be due to the grain refinement at 70℃ for 24 h (cold treatment condition).…”
Section: Introductionmentioning
confidence: 99%
“…Tahir et al [15] used a wire electric discharge machine to study the effects of cold treated(CT) and non-cold treated(NCT) brass wire electrodes on machining hardened (HSLA) steel. (CT) brass wire generates a smoother surface finish than (NCT) brass wire, and(NCT) brass wire creates a lower kerf width, according to the research.…”
Section: On the Basis Of Types Of Wire Usedmentioning
confidence: 99%
“…Gong et al 14 have reported that the electrical parameters like peak current had the greatest effect than non-electrical parameters on surface roughness and machining time. Tahir and Jahanzaib 15 have conducted WEDM of high-strength low-alloy by both cold treatment and non-cold treated brass wires. It was found that pulse on time was the most contributing factor on cutting speed, surface roughness and kerf.…”
Section: Introductionmentioning
confidence: 99%